Designing a circular carbon and plastics economy for a sustainable future - Vidal, Fernando; van der Marel, Eva R.; Kerr, Ryan W. F.; McElroy, Caitlin; Schroeder, Nadia; Mitchell, Celia; Rosetto, Gloria; Chen, Thomas T. D.; Bailey, Richard M.; Hepburn, Cameron; Redgwell, Catherine; Williams, Charlotte K. (Nature (London), 2024)
The linear production and consumption of plastics today is unsustainable. It creates large amounts of unnecessary and mismanaged waste, pollution and carbon dioxide emissions, undermining global climate targets and the Sustainable Development Goals. This Perspective provides an integrated technological, economic and legal view on how to deliver a circular carbon and plastics economy that minimizes carbon dioxide emissions. Different pathways that maximize recirculation of carbon (dioxide) between plastics waste and feedstocks are outlined, including mechanical, chemical and biological recycling, and those involving the use of biomass and carbon dioxide. Four future scenarios are described, only one of which achieves sufficient greenhouse gas savings in line with global climate targets. Such a bold system change requires 50% reduction in future plastic demand, complete phase-out of fossil-derived plastics, 95% recycling rates of retrievable plastics and use of renewable energy. It is hard to overstate the challenge of achieving this goal. We therefore present a roadmap outlining the scale and timing of the economic and legal interventions that could possibly support this. Assessing the service lifespan and recoverability of plastic products, along with considerations of sufficiency and smart design, can moreover provide design principles to guide future manufacturing, use and disposal of plastics. Four future greenhouse gas emission scenarios for the global plastics system are investigated, with the lead scenario achieving net-zero emissions, and a series of  technical, legal and economic interventions recommended.